Nem tudo que reluz é ouro: oficinas terapêuticas no cenário da Reforma Psiquiátrica - Cerqueira, Ariadne Cedraz (2006)
The purpose of this study is to discuss the therapeutic workshops function, while questioning if they constitute a mechanism for change of the traditional asylum logic. The Psychiatric Reform was materialized with the financing and regulation of alternative services that substitute the psychiatric hospital. This change was promoted by the anti asylum debate and the deinstitutionalization besides psychosocial rehabilitation paradigms. Mental health care, therefore, acquired a new form and the Centers for Psychosocial Care (CAPS) are considered the main services of the health network presently under construction. They are services that offer a variety of therapeutics and amongst them is the workshop, considered essential for the advancement of the Reform ideas. The study was conducted in a CAPS II in Natal, RN. Systematic visits were made using the Institutional Analysis perspective, futhermore were made interviews with professionals who was related to workshops. In the end, data were then discussed according to Schizoanalysis. Results denot that workshops represents, in the same time, progress and regress of Psychiatric Reform. It was observed that workshops were oftentimes reduced to strategies for the occupation of time, and as a means for the transmission of social values considered correct. The relationship between professionals and the user of the service was hierarchical and both players was seeing the workshop as a task to be met. Although users expressed intreresting about wokshops, was reported that the work was boring. Besides, except for some cases, the therapeutic workshops wasn t helping clients to create other possibilites in theirs life and stops the job inside the mental care service